KONSERVASI AMFIBI DI INDONESIA: MASALAH GLOBAL DAN TANTANGAN1) (Conservation of Amphibian in Indonesia: Global Problems and Challenges) - Mirza D Kusrini (Media Konservasi, 2007)
This paper reviews potential causes of amphibian population declines in Indonesia in relation to global amphibian declines. At least six factors were identified: over-harvesting, loss of forest and wetland habitats, pollution, disease, introduction of exotic species and deformities. The conservation of Indonesian amphibian faces many challenges, among other the low perception and knowledge about amphibian among general public, also low number and low quality of local herpetologist .Key word: global amphibian declines; amphibian; frog; Indonesia